RANCANG BANGUN APLIKASI MANAJEMEN GUDANG SUKU CADANG ALAT BERAT PNJ - Abdul Azis Abdillah; Muhammad Toby Adigunanugraha; Ivana Bianca (Politeknik Negeri Jakarta, 2019)
Heavy Equipment Study Program, Jakarta State Polytechnic, has a warehouse that aims to store spare parts. These spare parts are used to meet the practical needs of students when lectures take place every semester. During this time, to lend and report spare parts, heavy equipment warehouse technicians still use forms and spare parts cards. This method is less effective when the stakeholders such as the Head of Workshop and Head of Study Program want to know the amount of spare parts stock that is still owned by the warehouse or data warehouse cannot be seen in real time. From these problems, the warehouse needs a way to speed up the process. One method that can be used to overcome this problem is to create a web-based system or application that can carry out an inventory, record, process, and report the spare parts data contained in the heavy equipment warehouse. This writing aims to design and build warehouse management applications for heavy equipment spare parts. So, with this web-based application, stake holders can view reports from the warehouse with the right target, accurate, and efficient.